Pooled analysis safety profile of nivolumab and ipilimumab combination therapy in patients with advanced melanoma - Sznol, Mario; Hassel, Jessica C. (Journal of clinical oncology, 2017)
PurposeThe addition of nivolumab (anti-programmed death-1 antibody) to ipilimumab (anti-cytotoxic T-cell lymphocyte-associated 4 antibody) in patients with advanced melanoma improves antitumor response and progression-free survival but with a higher frequency of adverse events (AEs). This cross-melanoma study describes the safety profile of the approved nivolumab plus ipilimumab regimen.MethodsThis retrospective safety review on data from three trials (phase I, II, and III) included patients with advanced melanoma who received at least one dose of nivolumab 1 mg/kg plus ipilimumab 3 mg/kg every 3 weeks × 4 and then nivolumab 3 mg/kg every 2 weeks until disease progression or unacceptable toxicity while following established guidelines for AE management. Analyses were of all treatment-related AEs, select (immune-related) AEs, time to onset and resolution, and use of immune-modulating agents and their effects on outcome.ResultsAmong 448 patients, median duration of follow-up was 13.2 months. Treatment-related grade 3/4 AEs occurred in 55.5% of patients; 35.7% had treatment-related AEs that led to discontinuation. The most frequent treatment-related select AEs of any grade were skin (64.3%) and GI (46.7%) and of grade 3/4, hepatic (17.0%) and GI (16.3%); 30.1% developed a grade 2 to 4 select AE in more than one organ category. Median time to onset of grade 3/4 treatment-related select AEs ranged from 3.1 (skin) to 16.3 (renal) weeks, and with the exclusion of endocrine AEs, median time to resolution from onset ranged from 1.9 (renal) to 4.5 (pulmonary) weeks, with resolution rates between 79% and 100% while using immune-modulating agents. Four (< 1%) on-study deaths were attributed to therapy.ConclusionFrequency of grade 3/4 treatment-related AEs was higher with nivolumab plus ipilimumab and occurred earlier than historical experience with either agent alone, but resolution rates were similar.
Published at jco.org on September 15, 2017
Gesehen am 22.06.2018